RANCANGAN BOOKLET WISATA KAWASAN SARIBU RUMAH GADANG DI KABUPATEN SOLOK SELATAN - SANDY KELANA, Dr. Syafwandi, M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Saribu Rumah Gadang (One Thousand Minangkabau Traditional Houses) Area is one of the tourism destinations in Nagari Koto Baru, Sungai Pagu Subdistrict, South Solok Regency. Rumah Gadanglocated in this area still looks authentic and quite well maintained despite being aged. The number of Rumah Gadang in this area is 192 units with various forms.The promotion of a tourism area can affect the number of tourists who visit the area. The problem that exists nowadays is the tourism promotion of SaribuRumahGadang Area has not been able to attract many tourists to visit and lack of information in the media campaign.The problem studied is how to design a promotional media in a form of informative and communicative Booklet by utilizing elements and principles of visual communication design. The purpose of this design to convey information, educate, and invite potential tourists to visit this tourism area. The design process starts from data collection, observation, interview and documentation. The method of analysis used in this design is SWOT analysis, this analysis is chosen to know the strengths and opportunities in designing the media campaign and evaluate the weakness and threats that might exist.The supporting media used in the Booklet design of Saribu Rumah Gadang Area in South Solok District are guest book, T-shirts, flyers, stickers, digital posters, totebag, pins, and hats.Keyword: Saribu Rumah Gadang Area, Booklet, Promotion Media.